Cartas al Papa: modelos epistolares en los manuales de correspondencia de los siglos XVI-XVII - Carmen Serrano Sánchez (2018)
The spreading of letter-writing and its social implication during the Modern Age resulted in the appearance of books in vernacular languages to learn how to write a letter correctly from the mid-Sixteenth century in Spain, as well as the rest of Europe. Among the varied examples offered to the readers to adapt their correspondence to the customs and conventions of this time, it’s possible to find some letters directed to the Pope, who certainly had to be one of the most demanding addressees. In these treatises the Pontiff not only appears as the absent to whom the missives are written, but he also sometimes takes the quill. This collection of model letters makes up a imaginary correspondence that must be studied from the perspective of the epistolary theory, analyzing the typologies of letters proposed, the epistolary topics and themes allowed – the matters that could be discussed directly with the Pope, and those other ones that required intermediaries –, the authorized senders and